Time‐Limited Loyalty Rewards. (29th November 2022) - Caminal, Ramon
Abstract : I examine an infinite‐horizon model in which a monopolist can commit to sell the good to repeat customers at a reduced price. Such an option may or may not expire. Consumer preferences are subject to temporary shocks, which implies that loyalty rewards can raise efficiency by contracting prior to private information arrival. I show that expiration dates enhance the effectiveness of loyalty programs by disciplining consumers, who otherwise would excessively delay the redemption of rewards, and reduce the frequency of purchases. Moreover, if firms can influence future regular prices then loyalty programs become more profitable, but may harm consumers.